2010
DOI: 10.1590/s1415-790x2010000300003
|View full text |Cite
|
Sign up to set email alerts
|

Inatividade física e fatores associados em adultos, São Paulo, Brasil

Abstract: Objective: To analyze the prevalence of overall and leisure time physical inactivity and associated factors and types of exercises or sports modalities according to schooling in 2,050 adults from 18 to 59 years of age -state of São Paulo, Brazil. Methods: Population-based cross-sectional study with a stratified sample of clusters performed in multiple stages. Physical inactivity was determined using the short version of the International Physical Activity Questionnaire -IPAQ and by a question on the regular pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
1
46

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(74 citation statements)
references
References 23 publications
3
22
1
46
Order By: Relevance
“…Sedentarism or insufficient leisure physical activity is associated with blood hypertension and diabetes 5,6 , with increase in the number of hospitalizations 7 . It is more prevalent in women 8 , elderly 1 and individuals with low educational level 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Sedentarism or insufficient leisure physical activity is associated with blood hypertension and diabetes 5,6 , with increase in the number of hospitalizations 7 . It is more prevalent in women 8 , elderly 1 and individuals with low educational level 5 .…”
Section: Introductionmentioning
confidence: 99%
“…In a population based study carried out in the State of São Paulo, Zanchetta et al 4 observed a physical inactivity rate of 12.9% among women aged between 18 and 29 years. Despite current recommendations and reported benefits for mother and child, physical activity, especially sports and exercise, decreases during pregnancy 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Em contrapartida, estudos que avaliaram o desfecho atividade física no domí-nio tempo livre, mostraram que a escolaridade têm obtido forte associação com o nível de atividade física entre trabalhadores 17,19 e da população como um todo 21,22 . Para estes estudos, adultos com maior nível educacional possuem melhor acesso ao conhecimento, além de condições materiais, o que facilita a prática e manutenção de hábitos saudáveis.…”
Section: Resultsunclassified
“…Os indivíduos em condição escolar e socioeconômica desfavorecidas tendem a residir mais distante do local de trabalho, em áreas menos seguras e desprovidas de locais próprios para a prática de atividade física. Além disso, o tempo que os mesmos gastam utilizando o transporte público, caminhando ou pedalando como meio de deslocamento entre a residência e o trabalho, restringe o tempo livre para atividades de lazer 22 .…”
Section: Resultsunclassified